Immunobiology of liver xenotransplantation. (September 2012) - Ekser, Burcin; Burlak, Christopher; Waldman, Joshua P; Lutz, Andrew J; Paris, Leela L; Veroux, Massimiliano; Robson, Simon C; Rees, Michael A; Ayares, David; Gridelli, Bruno; Tector, A Joseph; Cooper, David KC
Pigs are currently the preferred species for future organ xenotransplantation. With advances in the development of genetically modified pigs, clinical xenotransplantation is becoming closer to reality. In preclinical studies (pig-to-nonhuman primate), the xenotransplantation of livers from pigs transgenic for human CD55 or from α1, 3-galactosyltransferase gene-knockout pigs+/– transgenic for human CD46, is associated with survival of approximately 7–9 days. Although hepatic function, including coagulation, has proved to be satisfactory, the immediate development of thrombocytopenia is very limiting for pig liver xenotransplantation even as a 'bridge' to allotransplantation. Current studies are directed to understand the immunobiology of platelet activation, aggregation and phagocytosis, in particular the interaction between platelets and liver sinusoidal endothelial cells, hepatocytes and Kupffer cells, toward identifying interventions that may enable clinical application.